Brand Positioning untuk Keunggulan Bersaing pada Aplikasi Transportasi Online Menggunakan Sentiment Analysis (Studi pada: Go-Jek dan Grab) - Mufrihah Fitriyani; Tri Widarmanti (Universitas Batanghari Jambi, 2023)
The development of technology and information in the industrial revolution 4.0 an impact on the increasing number of internet users. Social media is a place to express opinions, share and receive information in a short time to produce User Generated Content (UGC). Not only individuals, but companies also use social media to interact with their customers to understand the company's position in the eyes of customers. Through brand positioning on social media, companies can compare with competing companies to measure their competitive advantage on social media. This study aims to determine the brand positioning and competitive advantage of the top brands of online transportation applications in Indonesia, namely Go-Jek and Grab via Twitter. The method used in this research is a mixed method. This study obtained data through crawling data on Twitter using RStudio version 4.2.2 software. The data processed in this study is UGC in the form of tweets with the keywords